2016
DOI: 10.1095/biolreprod.116.141861
|View full text |Cite
|
Sign up to set email alerts
|

Function and Hormonal Regulation of GATA3 in Human First Trimester Placentation

Abstract: Pregnancies resulting from fresh in vitro fertilization (IVF) cycles exposed to supraphysiologic estrogen levels have been associated with higher rates of low birth weight and small for gestational age babies. We identified GATA3, a transcription factor selectively expressed in the trophectoderm during the blastocyst stage of embryo development, in an upstream analysis of genes that were differentially methylated in chorionic villus samples between IVF and non-IVF infertility treatment pregnancies. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Conditions leading to infertility may be involved with abnormal placentation and trophoblast invasion. 22,74,75 The etiology of recurrent pregnancy loss may also come back to the trophoblast. Premature loosening of trophoblast connections and consequent premature and disorganized flow of maternal blood into the intervillous space have been associated with recurrent spontaneous abortion.…”
Section: Infertility and Abnormal Placentationmentioning
confidence: 99%
“…Conditions leading to infertility may be involved with abnormal placentation and trophoblast invasion. 22,74,75 The etiology of recurrent pregnancy loss may also come back to the trophoblast. Premature loosening of trophoblast connections and consequent premature and disorganized flow of maternal blood into the intervillous space have been associated with recurrent spontaneous abortion.…”
Section: Infertility and Abnormal Placentationmentioning
confidence: 99%
“…Adverse perinatal outcomes such as low birth weight newborn in term singletons have been associated with fresh IVF-ET because of the hyperestrogenic milieu generated during COS in IVF [7][8][9][10][11]. Excessive E2 priming induced from development and recruitment of multiple follicles can affect gene expression pattern change like Grb10 and GATA3, and generate epigenetic alterations in developing embryo and fetus through alterations in DNA methylation, histone alteration and others [27][28][29][30]. It is also reported that immune environment changed due to the increase of natural killer cells in oocytes during stimulated cycles compared with natural cycles [31].…”
Section: Discussionmentioning
confidence: 99%
“…Giorgetti et al found that PAPP‐A protein level was strongly negatively correlated with oestrogen level on the hCG day and that it played a key role in the invasion of trophoblast cells by increasing the tolerance of the intima to the foetus . In addition, a recent study showed that high oestrogen levels affect the expression of GATA3 in trophoblast cells, thereby affecting their migration, invasion and cultivation . Therefore, persistently high oestrogen levels during early pregnancy should be avoided in luteal support.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, a recent study showed that high oestrogen levels affect the expression of GATA3 in trophoblast cells, thereby affecting their migration, invasion and cultivation. 35 Therefore, persistently high oestrogen levels during early pregnancy should be avoided in luteal support.…”
Section: Discussionmentioning
confidence: 99%